The role of the polar head group and aliphatic tail in the self-assembly of low molecular weight molecules in oil. (October 2021) - Golodnizky, Daniel; Rosen-Kligvasser, Jasmine; Davidovich-Pinhas, Maya
Abstract: The current research explores the involvement of head group size, chemical group type, and aliphatic tail in the molecular self-assembly of various oil structuring agents with similar 18-carbon aliphatic chains and hydroxyl, carbonyl, and/or carboxyl groups, in canola oil. Thermal and mechanical analyses at different molar concentrations emphasized the involvement of van der Waals (vdW) interactions and hydrogen bonds (H-bonds) in the self-assembly process. Higher contribution of vdW-forces in the self-assembly was observed when increasing molecular concentration from medium to high. The presence of H-bonds corresponding with organized crystal structures was detected in samples containing hydroxyl or carboxyl groups using nano-structure analysis. Absence of such groups led to ordered organization only at high concentrations, implying the involvement of vdW interactions. Polarized images demonstrated curved structures for long head group molecules, implying the formation of intermolecular H-bonds with neighboring molecules leading to structure curvature. The current results provide experimental indication to involvement of different forces, i.e. H-bonds and vdW, in the molecular self-assembly of oil structuring agents in oil which can be further exploit while developing new oleogel system based on low molecular weight gelators. Graphical Abstract: ga1 Highlights: Both polar head group and aliphatic tail are involved in the self-assembly of gelators in oil. van der Waals interactions are more significant at high concentrations. Hydrogen bonding ability is directly related to the amount of hydroxyl groups in the molecule. Long hydroxyl head group can form intermolecular hydrogen bonds leading to structure curvature.